On the security of RSA textbook signature scheme on Paillier ciphertext - Mihalkovich, Aleksejus; Sakalauskas, Eligijus (Lietuvos matematikos rinkinys, 2016)
In this paper we consider Pailler encryption and RSA textbook signature. We show that due to valuable homomorphic property these algorithms can be used together to obtain a valid signature on a certain combination of ciphertexts. Our goal is to show that this combination of algorithms provide security against chosen plaintext and chosen ciphertext attacks.
Keywords: security analysis; e-signature; asymmetric encryption